If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2 + x = -2 Reorder the terms: 2 + x + x = -2 Combine like terms: x + x = 2x 2 + 2x = -2 Solving 2 + 2x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2x = -2 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = -2 + -2 2x = -2 + -2 Combine like terms: -2 + -2 = -4 2x = -4 Divide each side by '2'. x = -2 Simplifying x = -2
| 6x-1(5x+5)=-8-2(x+12) | | 7-1/3 | | 6*9=n | | 6*8=n | | 5/4x-5/6x | | 3x+3=23-7x | | 3x+1/2(4x+8) | | 16x-6x-2x=0 | | 12(0)-6(3)=-18 | | 2x+(-2)*y=12 | | A*a=B*b | | 12(1)-6(5)=-18 | | 8s+2s=70 | | 6n-9=-62 | | 12(-2)-6(1)=-18 | | 6n-9=-57 | | factorx^4-8x^2+7=0 | | y/19=-5 | | -7k+9=56 | | 11.7x=46.8 | | -7k+9=49 | | -7k+9=44 | | 3-10k=26 | | 3-10k=13 | | 9-y=5x+3 | | 3-10k=10 | | 3-10k=5 | | 14-3n=4n | | 6y+2=88y-4 | | x^2+22x-23=180 | | -4y=12x-32 | | 3-10k=3 |